Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Kepemilikan Asing, dan Kepemilikan Keluarga terhadap Penghindaran Pajak - Evi Nurjana Mujid; Rochmad Bayu Utomo (Jurnal Penelitian Ekonomi Akuntansi, 2024)
The aim of this research is to determine whether managerial ownership, institutional ownership, foreign ownership and family ownership have an influence on tax avoidance. The population used in this research is all manufacturing companies listed on the Indonesia Stock Exchange in the 2013-2022 period. Using purposive sampling techniques, this research obtained 12 companies as research samples. The analytical method used in this research is multiple linear regression analysis, using SPSS. The results of this study show that managerial ownership, institutional ownership, and foreign ownership do not influence management activities in tax avoidance, while family ownership influences management activities in tax avoidance. The research employs publicly disclosed financial statement data, which may lack accuracy or completeness, data cleaning is performed using oulier elimination techniques, potentially excluding relevant insights and influencing the analysis outcomes. Future research is recommended to incorporate additional data, such as audited tax report, conduct comparative analysis of financial statement data across multiple years to detect consistent patterns, and utilize alternative calculation indicators to identify tax avoidance activities.